Effect of lipid nanoparticle formulations on skin delivery of a lipophilic substance - Vidlářová, Lucie; Hanuš, Jaroslav; Veselý, Martin; Ulbrich, Pavel; Štěpánek, František; Zbytovská, Jarmila (European journal of pharmaceutics and biopharmaceutics, 2016)
The aim of this study was to follow the skin penetration of a model lipophilic compound (Nile red) delivered by nanoparticulate carriers, the so-called lipid nanocapsules. The nanocapsules consisting of an oil core stabilized by amixture of surfactants were prepared by the phase inversion temperature method. Varying the particle composition (the oil/surfactant ratio) nanoparticles of different size were prepared and characterized. The penetration profile of Nile red delivered into the porcine skin by the nanoparticles compared to non-particulate samples was determined using fluorescence microscopy combined with a novel, statistically robust quantitative image analysis method. This study demonstrated that lipid nanoparticles promoted the skin penetration of encapsulated Nile red in comparison with all the non-particulate samples. Nile red delivered by the lipid-based nanoparticles was able to diffuse across the stratum corneum and partition itself uniformly in the epidermis. No relationship between Nile red penetration into the skin and the particle size was found. Moreover, the presence of sodium chloride in the water phase had a negative impact on the Nile red penetration into the skin. The results indicate that the physico-chemical circumstances of the nanoparticulate formulation play the major role in the penetration of lipophilic substances into the skin.
Keywords: Animals; Microscopy, Electron, Transmission; epidermis; oleje; velikost částic; Oils; Epidermis; Phase inversion temperature method; Microscopy, Fluorescence; Nile red; Surface-Active Agents; Particle Size; Oxazines; Nanoparticles; lipidy; Drug Carriers; Nanocapsules; software; Skin Absorption; Image analysis; prasata; kůže; kožní absorpce; Lipids; Lipid nanoparticles; nanočástice; fluorescenční mikroskopie; počítačové zpracování obrazu; Skin; Swine; Drug Delivery Systems; Skin penetration; nanokapsle; oxaziny; nosiče léků; Software; povrchově aktivní látky; lékové transportní systémy; transmisní elektronová mikroskopie; zvířata; Microscopy, Confocal; konfokální mikroskopie; Image Processing, Computer-Assisted